Study of Thyroid Hormone Status in Normal Newborn and Preterm, Low Birth Weight Baby (KYAMC Journal, 2017)
Background: Screening for thyroid hormones in the newborn baby is extremely important to detect the newborns who are borned with hypofunctional state of thyroid gland. This screening program in first few weeks of life is essential to prevent serious complications of hypothyroidism in future such as mental retardation.Objective: To assess the thyroid hormone levels in normal newborn and preterm, low birth weight babies and comparison of thyroid dysfunction between these two groups.Method: This cross - sectional analytical type of study was conducted in the department of physiology and paediatrics of Rajshahi Medical College & Hospital (RMCH) from July 2015 to June 2016. A total of 70 newborn baby were enrolled by systematic sampling of which 40 were normal healthy newborn and 30 were preterm, low birth weight babies. Data was collected from the parents and they were filled out standard questionnaire. Then venous blood was collected from each and every neonate and blood was sent to laboratory for estimation of thyroid hormone levels. FT4 and TSH values were estimated as these two are the most important parameters for determination of thyroid function.Result: In this study, the mean (±SD) serum FT4 level in term and preterm neonates were 14.17±2.14 and 12.25±3.16 (pg/ml) respectively. This FT4 value is significantly higher in term neonates than preterm neonates (P